Increasing surgical wait time does not increase the risk of node positive prostate cancer: Implications for surgical planning during the COVID-19 pandemic and beyond - Zaliznyak, Michael; Horwitz, Rainey; Davaro, Facundo; Rosen, Geoffrey H.; Murray, Katie S.; Hamilton, Zachary (Frontiers in Urology, 2023)
PURPOSE Prostate cancer (PCa) is a heterogeneous diagnosis, with a significant latency between diagnosis and risk of cancer specific mortality. During the COVID-19 pandemic, the need to balance the risk of COVID-19 exposure and resource allocation resulted in delays in non-emergent surgeries. We sought to assess if delays in surgical wait time (SWT) result in an increased risk of disease progression in the setting of clinically node positive PCa. MATERIALS & METHODS The National Cancer Database was queried for patients with cT1-3N0-1M0 PCa who underwent radical prostatectomy with lymph node dissection from 2010 to 2016. Patients were grouped based on pathologic node status (pN0 versus pN1). Outcomes including clinical tumor characteristics, hospital readmissions, and survival was correlated with length of SWT prior to radical prostatectomy. RESULTS A total of 218 patients with pN0 PCa and 805 patients with pN1 PCa met our inclusion criteria and were included in this study. Hospital length of stay and 30-day readmissions were similar between pN0 and pN1 patients. No significant association was detected between increased SWT and pN1 status among our patient population. Sensitivity multivariable analyses including only patients with Gleason 7-10 and excluding those who received androgen deprivation therapy prior to surgery showed similar findings that SWT was not associated with pN1 disease. With short term follow up, Kaplan-Meier analysis showed no significant difference in overall survival when stratified by SWT at 30-, 60-, 90-, or >90-day intervals. CONCLUSION With the impact of the recent pandemic on healthcare and hospital systems, it is important to understand the effect that likely delays in SWT can have on patient outcomes. The findings described in this study suggest that delays in SWT may not result in adverse nodal disease progression among patients diagnosed with pathological node positive PCa. These results will be important to share with patients and their families when discussing treatment options and can result in improved patient outcomes and satisfaction with treatment regimens.